Impacts of High Temperatures on the Growth and Development of Rice and Measures for Heat Tolerance Regulation: A Review - Jianghui Yu; Tianyu Du; Ping Zhang; Zhongtao Ma; Xi Chen; Jiale Cao; Hongjin Li; Tao Li; Ying Zhu; Fangfu Xu; Qun Hu; Guodong Liu; et al. (Agronomy)
As one of the world’s principal food crops, rice sustains over half of the global population. With global climate change intensifying, the frequency of extreme high temperatures is increasing, posing significant threats to the growth and development, yield, and quality of rice, thereby jeopardizing global food security. This study reviews the impacts of high temperatures on rice at different developmental stages and summarizes previous research on heat tolerance cultivation techniques for rice. Currently, to enhance heat tolerance in rice, the following strategies were primarily adopted: (1) the exploration of heat-tolerant genetic resources and breeding of heat-tolerant varieties; (2) cooling through canopy temperature management via enhanced transpiration regulated by water management; (3) the scientific application of fertilizers to promote the accumulation of assimilates in rice; (4) the application of exogenous regulators to bolster the antioxidant capacity of rice. The implementation of these strategies not only helps to ensure rice yield and quality but also provides robust support for addressing the challenges that global warming poses to agricultural production.